Presbeia Theotokou The Intercessory Role of Mary across Times and Places in Byzantium (4th - 9th Century) - Külzer, Andreas (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The present book is dedicated to one main aspect of the Marian cult: it investigates the historical process that made Mary, mother of Jesus, the most prominent intercessor across the Byzantine Empire at the end of Iconoclasm (843). The study touches religious and social issues, it refers only to contemporary ideas and sources and distinguishes itself consciously from later mariological concepts.